A Summary of Soil Hydrophobicity Trials in U.S. Golf Course Greens. Issue 1 (1st January 2013) - McMillan, Mica; Kostka, S.J.; Williams, K.E.; Cisar, J.L.; Boerth, T.
Abstract : Recommendations for golf course green construction have been for rootzone mixes with at least 90% sand while the remainder is typically peat or other organic material. This type of construction mix initially facilitates water movement through the profile but provides an environment conducive to soil hydrophobicity. Several factors such as sand texture, frequent wet to dry cycles, and accumulation of organic matter and thatch contribute to the development of soil water repellency in golf course greens. In research studies conducted over the past fifteen years in several locations across the United States, water drop penetration tests (WDPT) on golf greens have shown slightly and strongly water repellent soil is prevalently found at 0 and 1 cm depths. In the majority of locations, as the depth of profile increased, soil hydrophobicity decreased and was mostly non‐existent at the 6 cm depth. These results suggest that despite soil texture and management practices, soil hydrophobicity in a managed turfgrass area is most severe in the thatch and mat area of the profile. While the knowledge of what contributes to water repellency is critical for alleviating symptoms associated with hydrophobic coatings, management practices may be more successful if the focus was on the depth of the repellency.